(3GdVYaGAs - (3CHh LYaQ eMeO Hf YeQh Hf ehSi Hf MeGO GdYbjdj Gdecj, GdYbjdj,J (B332 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hUdhGJg Ydi fHjg eMeO hBdg hSde , hgh MSHfG hcai hdGbhI EdG Hg (B, (3HGH JHjf CMhGd ef fbd Yfg GdMOjK , eef de jfbd Ydi UMI s
(3eYGQVI Ydi fSNI GdMGaX CHj GdHQcGJ GdCfeGWis
(3hgj fSNI UGMHgG YHO GdQMef Hf eMeO Hf ESMGb Hf eMeO Hf jMji Hf eSfOgs
(3hYdjgG SeGYGJ cKjQI dHYV GdYdeGA ai (B486(3Us
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B319s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B95 s
Keywords: (3GdJGQjNs